Menggali Potensi Pajak PPh Pasal 22 Bendaharawan Pada UPT Satuan Pendidikan 10 SMP Negeri Kota Tangerang - Irma Novida; Erion Erion (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2020)
Income tax is is collected by the government treasurer, including the treasurer of the central government, regional government, government agencies or institutions, and other state institutions, namely with regard to payment for the delivery of goods, including the understanding that the treasurer is is obliged as the cash holder and other officers carry out the same function. This study aims to study and analyze the process of collection and deduction, to find out how much and how to report the deduction of income tax at the Yunior Hight School institution in Tangerang for the year of 2017 and 2018. The results of this study can be concluded that the process of withholding and collecting tax income on the procurement of goods at a rate of 1.5% in accordance with tax regulations and the treasurer does not report the periodic report on the purchase of goods in 2017 to the local Tax Service Office (KPP). The institution withholding and collecting PPh Article 22 is appropriate based on Law Number 36 of 2008.